Linking leadership to student learning - Leithwood, Kenneth A.; Louis, Karen Seashore; Anderson, Stephen E. (San Francisco : Jossey-Bass, 2011)
'Leadership is second only to classroom instruction as an influence on student achievement. Strong leadership can potentially unleash latent capacities that already exist in an organization. The authors, after five years of research, could not find a single documented case of a school that managed to turn around its student achievement trajectory in the absence of talented leadership. This thoroughly researched book examines all types of leaders: from the school principal to the teacher leader. The authors also look closely at each organizational level in the school system--school, classroom, community, district, and state'-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Educational leadership; School management and organization; Achievement motivation in children